Transitioning Vocational Education and Training in Africa: A Social Skills Ecosystem Perspective VET Africa 4.0 Collective - McGrath, Simon; Openjuru, George Ladaah; Lotz-Sisitka, Heila; Allais, Stephanie; Zeelen, Jacques; Wedekind, Volker; Ramsarup, Presha; Monk, David; Metelerkamp, Luke; Russon, Jo-Anna; Kyaligonja, Bonaventure; Robbins, Glen; et al. (Bristol Studies in Comparative and International Education, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book takes an expansive view of vocational education and training. Drawing on case studies across rural and urban settings in Uganda and South Africa, the book offers a new way of seeing this through an exploration of the multiple ways in which people learn to have better livelihoods. Crucially, it explores learning that takes place informally online, within farmers’ groups and in public and private education institutions.